1992
DOI: 10.1002/pssb.2221710116
|View full text |Cite
|
Sign up to set email alerts
|

Features Peculiar to Transport Phenomena in Cobalt‐Doped HgSe Crystals

Abstract: On Hg,-,Co,Se (5 x lo-' 2 x 2 1 x lo-*) crystals the Hall coefficient, resistivity, and Shubnikovde Haas oscillations of transverse magnetoresistance are measured. Experimental findings permit the conclusion that in mercury selenide, cobalt atoms form a resonance donor level. However, by contrast with mercury selenide crystals doped with iron and chromium, the cobalt impurity does not lead to the known electron mobility "anomaly" due to the ordering of the system of charged impurities. Shubnikov-de Haas oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As a result of an analysis of the experimental dependence C(N Ni ) with the use of Eq. ( 2) it was found that a variant of the single ionization (ν = 1, S io = 3/2) for the Ni 3+ (3d 7 ) ion does not agree with the experimental data, since it leads to the value n 0 ≈ 2.2•10 18 cm -3 which exceeds the known Hall concentration [8]. Second variant (ν = 2, S io = 2) for the Ni 4+ (3d 6 ) ion state corresponds to the value n 0d ≈ 2.5•10 18 cm -3 which correlates with the observed Hall concentration, however, gives the value of the S io ion core spin which is different from the approved value (5/2).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…As a result of an analysis of the experimental dependence C(N Ni ) with the use of Eq. ( 2) it was found that a variant of the single ionization (ν = 1, S io = 3/2) for the Ni 3+ (3d 7 ) ion does not agree with the experimental data, since it leads to the value n 0 ≈ 2.2•10 18 cm -3 which exceeds the known Hall concentration [8]. Second variant (ν = 2, S io = 2) for the Ni 4+ (3d 6 ) ion state corresponds to the value n 0d ≈ 2.5•10 18 cm -3 which correlates with the observed Hall concentration, however, gives the value of the S io ion core spin which is different from the approved value (5/2).…”
Section: Resultsmentioning
confidence: 84%
“…The symbols are the experimental values; the solid line is the theoretical fit to Eq. (2).At last it is the variant of three-fold ionization (ν = 3) for the Ni 2+ (3d8 ) ion state that leads to good approximation of the observed dependence C(N Ni ) and to the values of effective spin S i = (1.01 ± 0.04) and the concentration of donor electrons n 0d ≈ 0.2•10 18 cm -3 . The corresponding fitting dependence obtained by the equation (2) and the experimental values of the Curie constant for HgSe:Ni are depicted in Fig.2.In this case the charge state of the Ni 2+ ion corresponds to a situation, when the nickel atoms in the crystal lattice of HgSe are isovalent substitution impurities and, analogously to the Fe 2+ and Co 2+ ions[9], form the donor energy levels in the conduction band of the semiconductor matrix…”
mentioning
confidence: 66%